2010
DOI: 10.1021/np100240y
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Prevents Unloading-Derived Disused Muscle Atrophy by Attenuating the Induction of Ubiquitin Ligases in Tail-Suspension Mice

Abstract: The effects of quercetin (1) were investigated on disused muscle atrophy using mice that underwent tail suspension. Periodic injection of 1 into the gastrocnemius muscle suppressed muscle weight loss and ubiquitin ligase expression. Compound 1 reduced the enhancement of lipid peroxidation in the muscle. Injection of N-acetyl-l-cysteine, but not flavone (2), also prevented muscle weight loss and enhancement of lipid peroxidation. These findings demonstrate that 1 can prevent disused muscle atrophy by attenuatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 17 publications
1
49
0
Order By: Relevance
“…In recent years, the effects of flavonoids on muscle atrophy under various conditions have received increased attention. Quercetin has been shown to prevent obesity and disuse- induced muscle atrophy [49][50]. Baicalin and epigallocatechin-3-gallate were reported to attenuate skeletal muscle atrophy caused by cancer cachexia [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the effects of flavonoids on muscle atrophy under various conditions have received increased attention. Quercetin has been shown to prevent obesity and disuse- induced muscle atrophy [49][50]. Baicalin and epigallocatechin-3-gallate were reported to attenuate skeletal muscle atrophy caused by cancer cachexia [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary flavonoids are ubiquitously included in plant foods and have attracted considerable attention regarding their health effects (11,12). Previously, periodic injection of the flavonol-type flavonoid quercetin into the gastrocnemius muscle was shown to be effective in preventing muscle weight loss in mice that underwent tail suspension (11).…”
mentioning
confidence: 99%
“…Previously, periodic injection of the flavonol-type flavonoid quercetin into the gastrocnemius muscle was shown to be effective in preventing muscle weight loss in mice that underwent tail suspension (11). Furthermore, the principal flavonoid prenylation enabled naringenin, which is commonly found in grapefruit and sour oranges, to prevent muscle atrophy induced by disuse in denervated mice (13).…”
mentioning
confidence: 99%
“…The bulk of previous studies of quercetin in rodent models examining motor performance have employed models of defects rather than treatment of normal animals. As examples, various forms of quercetin supplementation in mice have attenuated the defects in motor function and morphology following chronic tail suspension [9], or denervation or crush of the sciatic nerve [10]. Likewise, quercetin treatment in murine genetic models of muscle dysfunction accompanied by motor impairments has also been effective [30].…”
Section: Discussionmentioning
confidence: 99%
“…Related to possible anti-aging effects, effects of quercetin have been examined on muscle function and atrophy in various animal models. For example, Mukai et al [9] used a tail suspension model to induce muscle atrophy in mice and reported that quercetin treatment suppressed markers of oxidative stress and attenuated muscle weight loss. In a follow-up study, Mukai et al [10] evaluated the effects of quercetin in a mouse model of disuse muscle atrophy involving denervation of the sciatic nerve.…”
Section: Introductionmentioning
confidence: 99%